Event Study: Pengumuman Laba Terhadap Reaksi Pasar Modal (Studi Empiris, Bursa Efek Indonesia 2008-2010) - , Rudianto Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A market will react to the information provided by the company. Whether it is information that is positive or negative, hence that it will create price equilibrium or balance. If there is new information to an issuer or a company then this information will be analyzed by the investor and if the market reacts quickly and accurately they create an efficient market. Abnormal return is the excess of return that actually happens to the normal return which is return expected by investors (expected return). Difference in return will be positive if the return received is greater than the return expected or calculated otherwise return will be negative if the return received is less than the return expected or calculated. In this study the profit announcement is an independent variable and Abnormal return is a dependent variable or variable that is affected. In this study, the samples used are a total of 29 LQ45 companies that went public on the Indonesia Stock Exchange with the observation period of 3 years (2008-2010). The samples used in this study are companies incorporated in LQ45 that meet some criteria for selecting the sample using purposive sampling method. The objectives of this research were: to measure the level of abnormal return investors received during the announcement period 2008 - 2010 both profit rise and profit fall. The results of this study indicate that abnormal return received by investor is not significant in the days surrounding the announcement, which is 5 days before the date of the announcement, and 5 days after the date of announcement of both profit rise and profit fall. Indonesia's capital market is not efficient in information in a semi-strong form for the period 2008 to 2010. Even though it is so, Indonesia capital market conditions have started to lead to a stronger form. This is proven most significantly at day -5 before the profits announcement. In general, investors react slowly to absorb information from the companies that publish their profits.